Unholy Wars : Afghanistan, Americe and International Terroorism - Cooley, John K (London Pluto Press, 1999)
To oppose the Soviet invasion of Afghanistan in 1979, the US formed an anti-communist alliance with militant Islamic forces in Central Asia. This book provides an account of this alliance and how the CIA planned and ran a holy war in Afghanistan.
Include Index and Map
Keywords: Terrorism -- United States -- Afghanistan -- Diplomatic relations -- Espionage, American